Kabyre, colosse, crocodile: images de Victor Hugo dans la Correspondance de Flaubert - Lőrinszky, Ildikó (Verbum – Analecta Neolatina, 2002)
The author of this study points out that Victor Hugo was the person Flaubert delt most with in his Correspondence. The contradictory images of Hugo in the letters of his younger collegue form alltogether a very complex way of approach to both writers. In this way the study shows the evolution of Falubert’s esthetic sense in comparison with the works of "père Hugo".